2021
DOI: 10.1186/s12992-021-00685-5
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon eye effect versus ripple effect: the role of family size on mental health during the COVID-19 pandemic in Pakistan

Abstract: Background The recent outbreak of COVID-19 has impacted adversely upon the mental health of millions of people worldwide. Impacts on the mental health conditions and the associated predictors relating to adults in Pakistan, the fifth most populous country in the world, during the COVID-19 remain understudied. Our aim was to investigate distress, anxiety, and overall mental health and their associated predictors among Pakistani adults in this pandemic. We specifically examine mental health issue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…A multinational, multicenter study showed that the prevalence of psychological adversity among HWs seems to be predicted by the HWs' medical history and whether they had physical COVID-19 symptoms, while being independent of the burden of COVID-19 cases within each country (38). There is extensive literature regarding the various factors related to mental health during the COVID-19 pandemic such as being single, separated, or widowed; a higher education level (39); a larger family size; loss of job; physical symptoms (40); and being in contact with potential COVID-19 patients were all associated with an increased level of depression, stress, and anxiety (41)(42)(43). Social distancing, being female, having chronic conditions, and living in the family with three to five members were associated with lower HRQOL scores (44).…”
Section: Discussionmentioning
confidence: 99%
“…A multinational, multicenter study showed that the prevalence of psychological adversity among HWs seems to be predicted by the HWs' medical history and whether they had physical COVID-19 symptoms, while being independent of the burden of COVID-19 cases within each country (38). There is extensive literature regarding the various factors related to mental health during the COVID-19 pandemic such as being single, separated, or widowed; a higher education level (39); a larger family size; loss of job; physical symptoms (40); and being in contact with potential COVID-19 patients were all associated with an increased level of depression, stress, and anxiety (41)(42)(43). Social distancing, being female, having chronic conditions, and living in the family with three to five members were associated with lower HRQOL scores (44).…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of 2020, the pandemic has had a great impact on the normal life of people in Latin America [ 2 , 3 , 4 ], including its largest country Brazil [ 5 , 6 ]. The COVID-19 pandemic not only threatens people’s health but also impacts on the mental health of the public [ 7 , 8 , 9 , 10 ]. On the one hand, the uncertainty of the initial route of transmission and treatment has exacerbated people’s fear during the COVID-19 crisis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the social distancing and confinement measures during the COVID-19 pandemic can lead to symptoms of anxiety and depression [ 12 , 13 , 14 , 15 , 16 , 17 ]. Although several studies have documented high prevalence rates of mental health symptoms in various parts of the world, especially in China [ 8 , 18 , 19 , 20 ], and early evidence of the mental impact of COVID-19 in Brazil was reported in a timely manner [ 21 ], there are few evidence-based studies containing critical predictors of mental issues in adults under a full-on COVID-19 outbreak in Brazil. As the devastating COVID-19 crisis continues in Brazil, it is crucial and urgent to investigate the risk factors for mental health issues in Brazilian adults.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of 2020, the pandemic has had a great impact on the normal life of people in Latin America [2][3][4], including its largest country Brazil [5,6]. The COVID-19 pandemic not only threatens people's health but also impacts on the mental health of the public [7][8][9][10]. On the one hand, the uncertainty of the initial route of transmission and treatment has exacerbated people's fear during the COVID-19 crisis [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the social distancing and confinement measures during the COVID-19 pandemic can lead to symptoms of anxiety and depression [12][13][14][15][16][17]. Although several studies have documented high prevalence rates of mental health symptoms in various parts of the world, especially in China [8,[18][19][20], and early evidence of the mental impact of COVID-19 in Brazil was reported in a timely manner [21], there are few evidence-based studies containing critical predictors of mental issues in adults under a full-on COVID-19 outbreak in Brazil. As the devastating COVID-19 crisis continues in Brazil, it is crucial and urgent to investigate the risk factors for mental health issues in Brazilian adults.…”
Section: Introductionmentioning
confidence: 99%